Model of Solving Economic Gap Through Share Waqf - Syamsuri Syamsuri; Annisa Silviana Yuniar; Nur Afifah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Economic inequality in Indonesia is growing with increasing poverty caused by unequal distribution. This can be seen in the number of poor people in 2020 reaching 27.55 million people compared to September 2019 reaching 24.79 million people. All government efforts to resolve economic disparities have been carried out, such as distribution of taxes, infrastructure, the flow of BLM funds, RPJMN. However, these efforts only prioritize large projects, so they have not been able to resolve the gap. Another effort is by waqf shares because the profits can be used for the benefit of the community which can be distributed evenly by the waqf manager. Share waqf is the use of funds from shareholders in the form of profits and capital distributed to waqf recipients by waqif in the form of employment, education, worship and other community needs. This study aims to determine the role of share waqf in resolving economic disparities. This study was written using a qualitative method with a literature review approach. Data collection comes from articles and books on gap settlement and the role of share waqf, as well as several government program reports. The data analysis technique used in this study is descriptive analysis. The results of this study can be concluded that share waqf has a role in resolving economic disparities by making the company's capital and stock dividends the object of waqf, then the wakif appoints a nadzir from the waqf institution to manage the waqf in the form of riil and non-riil sectors.